1993
DOI: 10.3168/jds.s0022-0302(93)77730-9
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Fat and Adipose Tissue Metabolism in Ruminants, Pigs, and Rodents: A Review

Abstract: Effects of dietary fat on dairy cows are reviewed. Dietary fat did not affect gain in BW or body condition score after peak lactation but tended to increase BW loss during early lactation and body fat deposition in growing cattle. Dietary fat decreased de novo fatty acid synthesis in adipose tissue. Basal FFA release from adipose tissue in vitro and beta-adrenergic lipolytic responses were increased by protected polyunsaturated fatty acids. Dietary fat increased body fat in growing pigs and decreased BW loss i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
207
7
44

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 311 publications
(288 citation statements)
references
References 184 publications
30
207
7
44
Order By: Relevance
“…For instance, in early lactating dairy cows it was expected that providing high-energy content feeds, such as dietary fat, would help in reducing body lipid mobilization through direct fat supply. Surprisingly, a meta-analysis of the data revealed that under this focus feeding practice cows mobilized more body lipids than unsupplemented ones (Chilliard, 1993).…”
Section: Effects Of Feeding Practices In Producing Animalsmentioning
confidence: 95%
“…For instance, in early lactating dairy cows it was expected that providing high-energy content feeds, such as dietary fat, would help in reducing body lipid mobilization through direct fat supply. Surprisingly, a meta-analysis of the data revealed that under this focus feeding practice cows mobilized more body lipids than unsupplemented ones (Chilliard, 1993).…”
Section: Effects Of Feeding Practices In Producing Animalsmentioning
confidence: 95%
“…Dietary energy source in dairy cattle 669 Several reviews have indicated nutrition to be important in the prevention and treatment of NEB related disorders [25, [47][48][49][50][51][52][53][54]. The relation of NEB with protein metabolism has been reviewed [25,47], just as the relation between dietary fat (C2 compounds or lipogenic) and metabolic and reproductive disorders [48,51,[54][55][56].…”
Section: Energy Metabolism In High-producing Dairy Cattlementioning
confidence: 99%
“…The relation of NEB with protein metabolism has been reviewed [25,47], just as the relation between dietary fat (C2 compounds or lipogenic) and metabolic and reproductive disorders [48,51,[54][55][56]. However, the key problem that occurs in the metabolism of a dairy cow in early lactation seems to be the unbalanced availability of C3 (glycogenic) and C2 (lipogenic) compounds derived from nutrients and body reserves.…”
Section: Energy Metabolism In High-producing Dairy Cattlementioning
confidence: 99%
See 1 more Smart Citation
“…This may explain the differential regulation of food intake according the nature of fatty acids although other mechanisms are likely to occur, such as gut peptide release during meals (Allen et al, 2005). The combined effects of an increase in milk energy secretion and a decrease (or no change) in energy intake paradoxically result in lower energy balance and higher body-weight loss in early lactation cows fed supplemental lipids (Chilliard, 1993). Furthermore, unsaturated fatty acids probably increased these effects since postruminally infused plant oil stimulated b-adrenergic lipolytic responses in adipose tissue (Gagliostro and Chilliard, 1991).…”
Section: Effect Of the Nature Of Nutrientsmentioning
confidence: 99%